082 Tailored learning for undergraduate student nurses using simulation to ease the transition from student to staff nurse. (December 2018) - Adair, E; Akers, E; Low, B; Bull, A
Abstract : The Great Ormond Street Clinical Simulation Centre (CSC) has introduced a bespoke programme of enhanced teaching via high and low fidelity simulation for undergraduate nurses. Anecdotal evidence suggests student nurses are struggling with a number of transitions from secondary school to student nurse and from student nurse to staff nurse. This programme directly addresses student anxiety, teaching fundamental nursing skills throughout the three-year nursing course. Through immersive simulation, skills are taught through tailored scenarios, which enable the students to acquire the physical, psychological and technical skills to provide nursing care. Scenarios covered: Anaphylaxis Sepsis Post–operative haemorrhage Aspiration pneumonia Febrile neutropenia Epilepsy Asthma Difficult parent These provide realistic and controlled environments to rehearse practical skills, time and medicine management alongside key aspects of care including such as escalation, communication and conflict resolution. The scenarios are tailored with specific learning objectives for each year. First-year students need to recognise the sick child. Second years need to recognise and respond. Third years on the cusp of qualifying need to recognise, respond and manage the sick child within their scope of practice. Feedback indicates that this simulation programme has given nursing students more preparation for clinical placements and the transition to staff nurse. Following this faculty support is essential in preparing students for their professional role (Thomas, 2015). Analysis of the results has shown that students have found simulation invaluable in establishing fundamental nursing skills while building confidence and competence. A common theme emerged that simulation has allowed for peer review and discussion through debriefing, enabling enhanced clinical communication skills and escalating concerns. Simulation has equipped students with transferrable skills that can be utilised throughout their training. Furthermore, students suggested scenarios that they would benefit from, drawing on clinical practice placement experience. The work undertaken has shown that simulation is key in preparing students for managing challenging clinical situations but also developing their resilience and retention